2018
DOI: 10.1002/smtd.201800022
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Thermoelectric Mg3Sb2 and Its Derivatives

Abstract: approaching their minimum, therefore fundamentally limits the availability for further improvements in these materials by this thermal strategy.This inspires the development of electronic strategies for zT enhancements in recent years. The strong coupling effect among S, σ, and κ e has led early strategies for electronic performance enhancement to mainly rely on the carrier concentration (n H ) optimization through chemical doping for nearly the past half of a century. [7] Till very recently, proven electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 88 publications
2
45
0
Order By: Relevance
“…The advances in n -type Mg 3 Sb 2- x Bi x demonstrate a good paradigm of how a new TE material can be rapidly developed and even transferred into the lab-scale module verification by the current TE community. In the past two years, there have been two timely review articles discussing the recent progress of Mg 3 Sb 2 and its derivatives: one is focusing on the design principle with a combination of theory and experiment [ 99 ] and the other on the manipulation of defects and electronic transport properties [ 100 ]. Readers who are interested in more details may refer to these two reviews.…”
Section: Introductionmentioning
confidence: 99%
“…The advances in n -type Mg 3 Sb 2- x Bi x demonstrate a good paradigm of how a new TE material can be rapidly developed and even transferred into the lab-scale module verification by the current TE community. In the past two years, there have been two timely review articles discussing the recent progress of Mg 3 Sb 2 and its derivatives: one is focusing on the design principle with a combination of theory and experiment [ 99 ] and the other on the manipulation of defects and electronic transport properties [ 100 ]. Readers who are interested in more details may refer to these two reviews.…”
Section: Introductionmentioning
confidence: 99%
“…N-Type Mg 3 Sb 2 -based Zintl compounds are a class of high-performance thermoelectric materials for the midtemperature application, recently discovered. Compared to the intrinsic p-type Mg 3 Sb 2 , the high performance of the n-type counterpart is mainly attributed to the excellent electronic conduction transports characterized by larger N V / m * ( N V and m * are the number of valleys and the band effective mass, respectively) . Mg 3.2 Sb 1.5 Bi 0.49 Te 0.01 with a peak zT of 1.51 at 716 K was first reported by Tamaki et al, and multiple groups have reported similar results. The role of excess Mg is to lift the Fermi level up toward the conduction band, and the Fermi level is further improved by Te doping, thus leading to a high n-type carrier concentration of ∼10 19 cm –3 and excellent thermoelectric transports. , …”
Section: Introductionmentioning
confidence: 99%
“…The low-temperature (<550 K) materials contain group-V alloys, [7] V 2 VI 3 , [8][9][10][11][12] CsBi 4 Te 6 , [13] and α-MgAgSb, [14] etc., in general exhibiting zT values below 1.5. The class of medium-temperature (550-950 K) materials contains many compounds, including IV-VI alloys, such as PbTe, [15,16] SnTe, [17] GeTe, [18] and SnSe, [19] I-V-VI 2 compounds, [20,21] Zintl compounds, [22] filled Skutterudites, [23] Clathrates, [24] Cu 2 Se, [25] and BiCuSeO, [26] to name a few. They normally embrace maximum zT values above 1.5.…”
mentioning
confidence: 99%